Self-Enforcing Agreements under Unequal Nationally Determined Contributions - Emilson C.D. Silva (Center for Economic Studies and ifo Institute (CESifo), 2016)
For a large global economy with normal goods, and an unequal world income distribution, we consider the endogenous formation and stability of an international environmental agreement (IEA) under nationally determined contributions (NDCs). Nations share green R&D efforts and enjoy R&D spillovers if they join an IEA. Nonmembers do not enjoy R&D spillovers. We show that the Grand Coalition is stable under NDCs if all nations are active carbon abatement and R&D contributors. If some nations are inactive, because they lack sufficient income to provide carbon abatement and R&D, the stable coalition under NDCs is the coalition of all active (wealthier) nations.
Keywords: D74; F53; H41; Q54; Q55; 330; international environmental agreements; self-enforcing; nationally determined contributions; R&D sharing